The Discovery of Oil And The Urgency of The Dutch Indies Mining Act 1899 - Setiawan, Agus (Fakultas Adab dan Humaniora, UIN Syarif Hidayatullah Jakarta, Indonesia, 2015)
AbstractThis article describes the historical background of the passing of the Dutch Indies Mining Act of or the Indische Mijnwet, the factors that led to the passing of the Act, and the obstacles and the responses of some parties to the act. Various factors that influenced the passing of the act were not separated from the changes within the political situation in The Netherlands and in the archipelago itself regarding the relationship between the Dutch and other powers, such as the British and local authorities, as well as the expansion of markets and production that were carried out by American oil companies in Asia. The American oil companiesâ€™ efforts to set foot in the Dutch Indies were a threat to the dominance of the oil companies in the Dutch Indies, and the Dutch Indies Mining Act was one legal obstacle for the existence and expansion of American oil companies that sought to dominate oil exploration in the Dutch Indies.—AbstraksiArtikel ini menjelaskan tentang latarbelakang sejarah pemberlakuan Undang-Undang Pertambangan Hindia Belanda Indische Mijnwet, yaitu faktor-faktor penyebab, dan hambatan-hambatan serta respon dari beberapa kelompok terhadap adanya Undang-Undang tersebut. Banyaknya faktor yang mempengaruhi pemberlakuan Undang-Undang tersebut tidak terlepas dari perubahan situasi politik di Belanda dan Indonesia Â yang masih memiliki keterkaitan hubungan antara Belanda dan para penguasa lainnya, seperti pemerintah Inggris dan pemerintahan setempat serta adanya eskpansi pasar dan produksi yang dibawa oleh perusahaan minyak Amerika di Asia. Adanya usaha-usaha perusahaan minyak Amerika untuk melebarkan sayapÂ ke Hindia Belanda menjadi sebuah ancaman terhadap dominasi perusahaan minyak bagi Hindia Belanda sendiri. Dan Undang-Undang Pertambangan Hindia Belanda merupakan salah satu masalah hukum terhadap keberadaan dan ekpansi perusahaan minyak Amerika yang akan mengeksplorasi minyak di Hindia Belanda.